Franciscan Philosophy in Chile: Two Main Exponents; [Filosofía Franciscana en Chile: Dos Principales Exponentes] - Caiceo-Escudero, J (University of San Buenaventura - Cali, 2019)
The Franciscan Order has been present in Chile since 1553 and this article includes two main philosophers: Alfonso Briceño Arias (1587-1668) and Eduardo Rosales Rojas (1906-1970). The first is known as the Second Escoto since his thinking is inspired by the famous English theologists (John Duns Scotus). The second one, Phd from the the Catholic University of Chile where he would eventually become an academic of Moral Theology. The purpose of this article is to analyze the philosophical thinking of both Chilean Franciscan theorists. This work is the result of a broader research on Franciscan Philosophy. To carry it out, the historical methodology was used reviewing primary and secondary sources as well as the philosophical analysis of the thinkers’ writings. © 2019, University of San Buenaventura - Cali. All rights reserved.